Enhancing arginase 2 expression using target site blockers as a strategy to modulate macrophage phenotype - Chiara De Santi; Frances K. Nally; Remsha Afzal; Conor P. Duffy; Stephen Fitzsimons; Stephanie L. Annett; Tracy Robson; Jennifer K. Dowling; Sally-Ann Cryan; Claire E. McCoy (Molecular Therapy: Nucleic Acids, 2022)
Macrophages are plastic cells playing a crucial role in innate immunity. While fundamental in responding to infections, when persistently maintained in a pro-inflammatory state they can initiate and sustain inflammatory diseases. Therefore, a strategy that reprograms pro-inflammatory macrophages toward an anti-inflammatory phenotype could hold therapeutic potential in that context. We have recently shown that arginase 2 (Arg2), a mitochondrial enzyme involved in arginine metabolism, promotes the resolution of inflammation in macrophages and it is targeted by miR-155. Here, we designed and tested a target site blocker (TSB) that specifically interferes and blocks the interaction between miR-155 and Arg2 mRNA, leading to Arg2 increased expression and activity. In bone marrow-derived macrophages transfected with Arg2 TSB (in the presence or absence of the pro-inflammatory stimulus LPS), we observed an overall shift of the polarization status of macrophages toward an anti-inflammatory phenotype, as shown by significant changes in surface markers (CD80 and CD71), metabolic parameters (mitochondrial oxidative phosphorylation) and cytokines secretion (IL-1β, IL-6, and TNF). Moreover, in an in vivo model of LPS-induced acute inflammation, intraperitoneal administration of Arg2 TSB led to an overall decrease in systemic levels of pro-inflammatory cytokines. Overall, this proof-of-concept strategy represent a promising approach to modulating macrophage phenotype.